2022
DOI: 10.35848/1347-4065/ac19fe
|View full text |Cite
|
Sign up to set email alerts
|

Development of plastic scintillators loaded with perovskite quantum dots

Abstract: We developed plastic scintillators loaded with perovskite quantum dots (QDs) to enhance the detection efficiency for high-energy photons such as X-rays and gamma rays. QDs with different emission wavelengths were loaded onto plastic scintillators at 5 wt%. The emission from the QDs only was observed in the radioluminescence spectra under X-ray irradiation. The photoluminescence decay behavior indicates that the absorption of the QD emission by the QDs themselves (self-absorption) results in long decay componen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 31 publications
0
13
0
Order By: Relevance
“…12 Second, because of the small dimensions of nanocrystals the near-edge exciton emission has high probability for escaping the volume of the nanocrystal without absorption. It is due to this second factor, that the excellent scintillation properties of these nanoparticles are best put to use when they are prepared as thin (B100 mm) films, 4,5,13,14 dispersed in a plastic matrix, 6,15,16 or other crystal hosts. 7,17 However, when it comes to the absorption of ionising radiation this method has a problem.…”
Section: Introductionmentioning
confidence: 99%
“…12 Second, because of the small dimensions of nanocrystals the near-edge exciton emission has high probability for escaping the volume of the nanocrystal without absorption. It is due to this second factor, that the excellent scintillation properties of these nanoparticles are best put to use when they are prepared as thin (B100 mm) films, 4,5,13,14 dispersed in a plastic matrix, 6,15,16 or other crystal hosts. 7,17 However, when it comes to the absorption of ionising radiation this method has a problem.…”
Section: Introductionmentioning
confidence: 99%
“…In order to optimize the PL and scintillation properties of the composite, we varied the perovskite mass loading in the nanocomposite disc from 1 to 10% with OAM 0.4 NCs. Higher loading of NCs containing high-Z atoms will produce a greater interaction with the incident X-rays and hence a larger detection efficiency. , However, the optical emission yield may be compromised due to greater optical scattering in those composites with higher percentage loading. The optical transmission of the CsPbBr 3 /PMMA composite decreases with an increase in loading concentration due to higher absorbance and scattering, as shown in Figure c.…”
Section: Resultsmentioning
confidence: 99%
“…37) Also, slow decay components appeared by the loading. 37) To avoid the self-absorption, in this study, we added wavelength shifting molecules to the perovskite QD-loaded plastic scintillators.…”
Section: Introductionmentioning
confidence: 97%
“…Utilizing fast and efficient emission of the perovskite QDs, several research groups have reported the development of plastic scintillators loaded with perovskite QDs. [32][33][34][35][36][37] However, owing to the small Stokes shift of the perovskite QDs and consequent self-absorption, the scintillation yield was reduced by the loading. 37) Also, slow decay components appeared by the loading.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation